Levels of Acetylcholinesterase and DNA Damage in Children Exposed to Organophosphate Pesticides in Tanjung Karang, Selangor, Malaysia - Nur Naqibah Lokhman; Zailina Hashim; Juliana Jalaludin; Ho Yu Bin; Vivien How; Nur Adibah Mohidem (Taylor & Francis, 2025)
This is an Accepted Manuscript of an article published by Taylor & Francis in International Journal of Environmental Health Research on 2025 available at: https://doi.org/10.1080/09603123.2025.2492367